Interferon-gamma- and perforin-mediated immune responses for resistance in the brain against Toxoplasma gondii - Suzuki, Yasuhiro (2011)
Toxoplasma gondii is an obligate intracellular protozoan parasite, which causes various diseases including lymphadenitis, congenital infection of fetuses and life-threatening toxoplasmic encephalitis in immunocompromised individuals. Interferon-gamma (IFN-γ)-mediated immune responses are essential for controlling tachyzoite proliferation during both acute acquired infection and reactivation of infection in the brain. Both CD4(+) and CD8(+) T cells produce this cytokine in response to infection. Murine models demonstrated that both CD4(+) and CD8(+) T cells are protective against reactivation of infection, although the latter have more potent protective activity. Various signaling molecules including MyD88, protein kinase C-theta, and nuclear factor-κB family transcription factors are important for T cells in inducing and/or maintaining their protective function. IL-12, IL-4, IL-6, IL-10, IL-17, IL-27, and IL-33 are involved in regulating resistance to T. gondii in the brain. IFN-γ can activate microglia, astrocytes, and macrophages and these activated cells control proliferation of tachyzoites using different molecules depending on the cell types and species of the host. IFN-γ also plays a critical role in recruitment of T cells into the brain after infection by inducing expression of adhesion molecule, VCAM-1, on cerebrovascular endothelial cells and of chemokines such as CXCL9, CXCL10 and CCL5. A recent study revealed that CD8(+) T cells are able to remove T. gondii cysts, the stage of the parasite in chronic infection, from the brain through their perforin-mediated activity. Thus, the resistance to cerebral infection with T. gondii requires a coordinated network utilizing both IFN-γ- and perforin-mediated immune responses. Elucidating how these two protective mechanisms function and collaborate in the brain against T. gondii will be crucial in developing a new method to prevent and eradicate this parasitic infection.